Translocation of cytoplasm and nucleus to fungal penetration sites is associated with depolymerization of microtubules and defence gene activation in infected, cultured parsley cells. - Gross, P (1993)
We describe a novel system of reduced complexity for analysing molecular plant-fungus interactions. The system consists of suspension-cultured parsley (Petroselinum crispum) cells infected with a phytopathogenic fungus (Phytophthora infestans) which adheres to a coated glass plate and thus immobilizes the plant cells for live microscopy. Conventional light and electron microscopy as well as time-lapse video microscopy confirmed the virtual identity of fungal infection structures and of several characteristic early plant defence reactions in the cultured cells and whole-plant tissue. Using this new system to approach previously unresolved questions, we made four major discoveries: (i) rapid translocation of plant cell cytoplasm and nucleus to the fungal penetration site was associated with local depolymerization of the microtubular network; (ii) the directed translocation was dependent on intact actin filaments; (iii) a typical plant defence-related gene was activated in the fungus-invaded cell; and (iv) simultaneous activation of this gene in adjacent, non-invaded cells did not require hypersensitive death of the directly affected cell.